A Critique of the Simultaneist Interpretation of Work Intensity in Marx's Value Theory from the TSSI perspective. (21st April 2023) - Deytha Mon, Alan A.; Sebastián Hdez. Solorza, A.
Abstract : This article makes an analytical critique of the position of Basu, Haas, and Moraitis, who, by extending the conventional linear system for the simultaneous determination of value, argue that in Marx's economic theory the intensification of work generates absolute surplus value and is not relative. This position is also contrasted with the original theory of Marx to verify its incompatibility. As an alternative in search of a rectification of the role of labor intensification as a generator of relative surplus value, this work incorporates labor intensity into the Temporal Single System Interpretation (TSSI), showing its full compatibility with Marx's original theory.